The effects of human resource practices, knowledge-oriented leadership and organisational innovation towards fourth industrial revolution: A review and research agenda / Choong Yuen Onn...[et al.] - Choong, Yuen Onn; Au Yong, Hui Nee; Charles, Ramendran SPR (Universiti Teknologi MARA, Kedah, 2019)
Ageing population and reduction in birth rates has altered the demographics’ structure on working-age populations. It has been a major setback for many developing countries especially at the era of digitalization. Hence, the purpose of this study is to investigate how fourth industrial revolution technology of the workplace and its societal challenges on business among productive aging workforce in Malaysia. The study is intend to conceptually argue that knowledge oriented leadership and human resource practices able to enhances organizational innovation where subsequently increase the compatibility of firm towards fourth industrial revolution. Based upon the discussion, a conceptual framework was developed. The adoption of quantitative study was proposed in order to examine the proposed model in the subsequent empirical study. It is expected that the results of the study would be able to generate some useful findings that provide valuable insight to business practitioners, policy makers, academicians and government at Ministry level.